The Impact of Self-Regulated Learning and Interpersonal Communication on Academic Procrastination Among Higher Education Students - Zulhadi Zulhadi; Zul Afdal (Indonesian Journal of Education and Social Studies, 2025)
This study aims to examine the influence of self-regulated learning and interpersonal communication on academic procrastination. Academic procrastination is a behavioral tendency of students to delay academic tasks, which can negatively affect learning outcomes and graduation rates. This research used a quantitative approach with a correlational design. The population consisted of 205 active students, selected through proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS. The results revealed that self-regulated learning has a negative and significant effect on academic procrastination with a regression coefficient of –0.180 and a significance value of 0.005 (<0.05). Meanwhile, interpersonal communication shows a negative but not significant effect on academic procrastination with a regression coefficient of –0.140 and a significance value of 0.130 (>0.05). Simultaneously, both variables contributed to the reduction of academic procrastination with a significant F-test result. These findings indicate that students with higher self-regulated learning tend to demonstrate lower procrastination behavior, while interpersonal communication, although negatively related, does not play a dominant role. The study concludes that strengthening students’ self-regulated learning abilities is essential to minimize academic procrastination within higher education environments.